UPAYA PENGELOLAAN EMOSI IBU PADA ANAK SELAMA PEMBELAJARAN DARI RUMAH (DAMPAK PANDEMI COVID 19) - Raihana Raihana (UIR PRESS, 2020)
One of the impacts of the Coved-19 pandemic is the implementation of learning from home by the government; this provides new jobs for parents, especially mothers. Where mothers have to accompany children in the teaching and learning process, on the other hand, mothers also have to do other household chores, this often creates negative emotions because of the enormous pressure the mother is facing. To reduce the pressure faced by mothers, it is necessary to make efforts to manage emotions when accompanying children to learn from home. The method used in this paper is a literature study, in which data collection techniques are obtained from books, literature, notes with the problem being solved. The results of the discussion in this paper are (1) Parents must learn to adapt to learning conditions from home. (2) Emotional therapy (3) Understand the child's abilities, children are ordinary humans who have limited learning abilities. (4) Relaxation, and (5) Discussion, before and after the learning takes place, the mother can invite the child to talk or discuss the learning being carried out.